Nepotistic Corruption Breeding For The Establishment Of A Political Dynasty - Syauket, Amalia (Green Publisher Indonesia, 2021)
Simultaneous Pilkada 2020 is still dwelling on the same pattern of problems from the previous Pilkada which actually experienced a significant increase in the journey of regional heads who came from the Political Dynasty. A total of 124 candidates are affiliated with political dynasties. One of them is caused by the double-edged sword of decentralization and regional autonomy. In addition to giving power to the regions in forming their own households, decentralization of regional autonomy triggers the decentralization of corruption that spreads to various regions which then drags the political elite. This is what causes regional autonomy to encourage oligarchic decentralization and the practice of political dynasties. The